Putting the scholar back into scholarship, the researcher into research, the knower into knowing, the entrepreneur into entrepreneurship . . .: A call to interiority - Futonge Nzembayie, Kisito (My University, 2025)
This essay challenges the prevailing externalist orientation of management scholarship by calling for a return to interiority: the attentive engagement of the researcher’s own knowing process. Anchored in Bernard Lonergan’s framing of the structure of human knowing, the authors argue that acts of experience, understanding, judgement, and decision are central to scholarly rigour but often remain unexamined. Through reflexive critique and philosophical grounding, the piece advocates for a scholarship that recognises the subjectivity of the knower as a source of insight rather than bias. By “putting the knower back into knowing,” the authors offer a compelling agenda for integrating first-person inquiry, reflexive training, and methodological innovation in doctoral education and academic research. The essay ultimately positions interiority as a means to enhance both the relevance and rigour of academic inquiry.
PUBLISHED
Keywords: interiority; scholarship; Bernard Lonergan, epistemology, interiority, scholarship; Inclusive Society; International Development; Manuscript, Book and Print Cultures; BUSINESS AND PHILOSOPHY; Entrepreneurship; Management Education; Specific learning difficulties; Education